Climate signals in carbon and oxygen isotope ratios of Pinus cembra tree‐ring cellulose from the Călimani Mountains, Romania. (31st October 2019) - Nagavciuc, Viorica; Kern, Zoltán; Ionita, Monica; Hartl, Claudia; Konter, Oliver; Esper, Jan; Popa, Ionel
Abstract: We analyse annually resolved tree‐ring stable carbon (δ 13 C) and oxygen (δ 18 O) isotopic chronologies from Swiss stone pine ( Pinus cembra L.) in Romania. The chronologies cover the period between 1876 and 2012 and integrate data from four individual trees from the Calimani Mts in the eastern Carpathians where climatic records are scarce and starts only from 1961. Calibration trials show that the δ 13 C values correlate with local April–May relative humidity and with regional to larger scale (European) summer precipitation. δ 18 O correlates significantly with local relative humidity, cloud cover, maximum temperature, as well as European scale drought conditions. In all cases, the climate effects on δ 13 C values are weaker than those recorded in the δ 18 O data, with the latter revealing a tendency toward higher (lower) values of δ 18 O during extremely dry (wet) years. The most striking signal, however, is the strong link between the interannual δ 18 O variability recorded in the Calimani Mts and large‐scale circulation patterns associated with North Atlantic and Mediteraneean Sea sea surface temperatures. High (low) values of δ 18 O occur in association with a high (low) pressure system over the central and eastern part of Europe and with a significantly warmer (colder) Mediterranean Sea surface temperature. These results demonstrate the possibility of using tree ring oxygen isotopes from the eastern Carpathians to reconstruct regional drought conditions in eastern Europe on long‐term time scales and larger scale circulation dynamics over the preinstrumental periods. Abstract : Our results demonstrate the possibility of using tree ring oxygen isotopes from the eastern Carpathians to reconstruct regional drought conditions in eastern Europe on long‐term time scales and larger scale circulation dynamics over the preinstrumental periods. The composite map between high δ 18 O (> 1 SD ) and summer sea surface temperature (SST). The hatching highlights significant values at a confidence level of 95%. Analysed period: 1876–2012.